Survey of Accounting, 9th Edition - Carl S. Warren; Amanda Farmer (Cengage Learning, 2020)
Now you can master the most essential topics in financial and managerial accounting today using the unique Integrated Financial Statement Framework in Warren/Farmer's SURVEY OF ACCOUNTING, 9E. Written specifically for readers who have no prior knowledge of accounting, this edition's distinctive framework illustrates the impact of transactions on financial statements without the use of debits and credits. The authors also incorporate Metric Analyses that clearly connect transactions and management decisions to metrics that assess the financial condition and performance of businesses today. Streamlined content throughout this edition and numerous examples from actual organizations further highlight the importance of accounting transactions on management decisions in businesses today. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.